THE ESTABLISHMENT OF GEOGRAPHICAL INDICATION PROTECTION COMMUNITY (GIPC) AS A LEGAL PROTECTION MSME’S PRODUCTS - Triyono Adi Saputro; Yudho Taruna Muryanto; Suraji Suraji (UNISSULA, 2021)
A geographical indication is a part of intellectual property rights (IPR), which plays an important role in international trade as a magnet for consumers for MSMEs' products. However, the geographical indication is still underestimated by MSME players; and therefore, this issue requires further attention and analysis as the efforts to study the essence and urgency of the Geographical Indication Protection Community (GIPC) in supporting the realization of legal protection in regencies and cities throughout Indonesia. To support the investigation process, a case-based approach is required with primary and secondary research material sources through literature studies that correlate with business actors, rule of law and government. This study is doctrinal or normative research with qualitative data analysis. Efforts to establish Geographical Indication Protection Community (GIPC) are significant in assisting local MSME players to register legal protection through geographical indications and bridge local MSME players, local government, and stakeholders in sharing resources or information that can increase product competitiveness in regencies and cities in Indonesia on both national and international market scales.